Clinicopathological Features Associated With the Prognosis of Patients With Adrenal Cortical Carcinoma: Usefulness of the Ki-67 Index. Issue 21 (May 2016) - Choi, Yun Mi; Kwon, Hyemi; Jeon, Min Ji; Sung, Tae-Yon; Hong, Suck Joon; Kim, Tae Yong; Kim, Won Bae; Shong, Young Kee; Lee, Jae Lyun; Song, Dong Eun; Kim, Won Gu
Abstract : Abstract: Adrenocortical carcinoma (ACC) is a rare tumor with a poor prognosis. Identification of clinicopathological features and molecular prognostic markers is important for the treatment of ACC. The aim of this study was to evaluate the clinical and histopathological features of ACC for prognostic prediction. This retrospective cohort study included 86 patients pathologically confirmed with ACC in a single center. Ki-67 index was evaluated by immunohistochemical staining of paraffin-embedded samples. The median age of the 86 (46 male and 40 female) patients with ACC was 49 years old (range 21–78), and the mean primary tumor size was 12.2 ± 5.2 cm. ACCs were incidentally found in 29 patients (34%). Three patients (3%) had bilateral ACC, and 59 patients (69%) had distant metastasis (37 synchronous and 22 metachronous). Twenty-four patients (28%) had symptoms from hormone excess or mass effects, and 25 patients (29%) had nonspecific symptoms. The 5-year survival rate for ACC was 28%. Sixty patients underwent surgical treatment, including 37 patients with an R0 resection. Tumor size, Ki-67 index, stage, and resection status were independently associated with overall survival by multivariate analysis. In patients with R0 resection, recurrence was significantly associated with larger tumor size and functional tumor. Tumor size, Ki-67 index, stage, and resection status are important prognostic indicators of survival in ACC patients.